Desain dan Implementasi Platform Manajemen Historis Harga Saham dengan Kurasi Data dan Analisis Teknikal - Indra Hidayatulloh (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2017)
Current research topics related to the stock is dominated by stock price prediction. To predict the stock price, it needs historical stock prices data. Many providers are providing the data, but not all of them free. Some providers that provide historical stock prices data for free are Yahoo Finance, Google Finance, Stooq, and the National Stock Exchange (NSE) of India. However, often there are differences in data between providers both in terms of availability, content, data formats, and so on. Thus, investors need to take data from some providers to be compared in order to obtain optimal analytical results. Therefore, this study builds data management platform to curate the historical stock prices data from the four data sources as well equipped with technical analysis to facilitate analysis of investment. In this study it was found that the data curation of historical stock prices for the four data sources can be performed with RDBMS technology as the database. However, there is a weakness that is less flexible when required adding additional data sources of unstructured data or have a different column. But, with the data from the four data sources that have been integrated, technical analysis can provide a broader picture the trend of stock price movements by comparing the results of the analysis for each data source.